Inhibition of Glycolysis Reduces Disease Severity in an Autoimmune Model of Rheumatoid Arthritis - Abboud, Georges; Choi, Seung-Chul; Kanda, Nathalie; Zeumer-Spataro, Leilani; Roopenian, Derry C.; Morel, Laurence (Frontiers in Immunology, 2018)
The K/BXN mouse is a spontaneous model of arthritis driven by T cell receptor transgenic CD4+ T cells from the KRN strain that are activated by glucose-6-phosphate isomerase (GPI) peptides presented by the H-2g7 allele from the NOD strain. It is a model of autoimmune seropositive arthritis because the production of anti-GPI IgG is necessary and sufficient for joint pathology. The production of high levels of anti-GPI IgG requires on the expansion of CD4+ follicular helper T (Tfh) cells. The metabolic requirements of this expansion have never been characterized. Based on the therapeutic effects of the combination of metformin and 2-deoxyglucose (2DG) in lupus models that normalized the expansion of effector CD4+ T cells. We showed that the CD4+ T cells and to a lesser extent, the B cells from KBN mice are more metabolically active than the KRN controls. Accordingly, preventive inhibition of glycolysis with 2DG significantly reduced joint inflammation and the activation of both adaptive and innate immune cells, as well as the production of pathogenic autoantibodies. However, contrary to the lupus-prone mice, the addition of metformin had little beneficial effect, suggesting that glycolysis is the major driver of immune activation in this model. We propose that K/BXN mice are another model in which autoreactive Tfh cells are highly glycolytic and that their function can be limited by inhibiting glucose metabolism.